Randomized controlled trial assessing two commercial weight loss programs in adults with overweight or obesity - L. M. Arterburn; C. D. Coleman; J. Kiel; K. Kelley; L. Mantilla; N. Frye; K. Sanoshy; C. M. Cook (Wiley, 2019)
Summary Objective Lifestyle interventions remain the cornerstone for obesity treatment. Commercial programs offer one weight loss approach, yet the efficacy of few such programs have been rigorously investigated. The purpose of this study was to evaluate the efficacy of two commercial weight‐loss programs, both utilizing pre‐portioned meal replacements (MRs) and different levels of behavioural support, compared to a self‐directed control diet in adults with overweight and obesity. Methods In this 16‐week study, participants were randomized to the low‐calorie OPTAVIA® 5&1 Plan® with telephone coaching (OPT), the reduced‐calorie Medifast® 4&2&1 self‐guided plan (MED), or a self‐directed, reduced‐calorie control diet. Differences in weight, body composition (DXA) and body circumferences, all measured monthly, were assessed by analysis of covariance with sex and baseline measures as covariates. Results Of 198 participants randomized (80.8% female, BMI 34.2 kg/m2, 45.7 years), 92.3% completed the study. The OPT and MED groups had significantly greater reductions in body weight (−5.7% and − 5.0%, respectively, p < 0.0001), fat and abdominal fat mass (p < 0.0001) and waist and hip circumferences (p ≤ 0.003) than control at 16 weeks. Weight change was correlated with MR usage and completion of coaching support calls. Conclusions Both structured commercial programs were more efficacious than a self‐directed, reduced‐calorie diet for weight loss and other anthropometric measures. Evidence‐based commercial programs can be an important tool to help adults with overweight and obesity lose clinically relevant amounts of weight.